Online-Based Management of New Student Admission Selection for Postgraduate Study Programs at State Islamic Colleges - Undang Syaripudin; Jaja Jahari (International Journal of Nusantara Islam, 2022)
Colleges are institutions that hold educational accounts. The role and information technology is in the management of human resources and students as the main customers in this education. The new student admissions information system is one of the information methods in higher education governance. Currently, the information technology infrastructure at UIN Sunan Gunung Djati Bandung is not sufficient to develop business process solutions using information systems. The purpose of this study is to create a new student information system architecture model by utilizing TOGAF ADM to describe business functions related to information systems. The design in this study uses the TOGAF model in the form of three parts. The first part is an analysis of the initial state of the organization, which includes Initial phase, requirements management, architectural vision, and business architecture. The second part discusses the enterprise architecture, which consists of two phases: information systems architecture and technology architecture. The third part is to find answers to enterprise architecture problems in the opportunities and solutions phase. The purpose of this research is to develop a strategy to ensure that the information system to be used is adaptable and that all activities related to new students are integrated with the information system. Blueprint vision of the new student admissions information system architecture is the need for a web-based information system. In addition, the blueprint business architecture and information systems architecture produce academic information systems that support the process of introducing new students. The blueprint technology architecture makes the design of the network infrastructure and server technology used. The blueprint of opportunities and solutions produces a solution gap analysis of the current system and an analysis of the results system that will be developed at UIN Sunan Gunung Djati Bandung